A report on the oral hygiene practices and oral health status of the negritos in botolan - How, R. Denise
It is the objectives of this paper to find out the oral hygiene practices of the Negritos in Botolan (the Masikap Settlement and to show their oral health status. Two parts were done to the study. The first consist of the interviews to find the oral hygiene practices and the second part is the oral examination. This study has shown that the Negritos also use the toothbrush in maintaining their oral hygiene. Indigenous materials such as salt and the guava twig however play a dominant role in their oral care. Frequency of oral hygiene practice is not very regular due mainly to the lack also financial difficulties.